Fiscal decentralization and water and sanitation provision: Evidence from Pakistan - Qayyum, Abdul; Lau, Wee-Yeap; Rahman, Nur Hairani Abd (Asian Journal of Economic Modelling, 2025)
Fiscal decentralization offers promise in enhancing the delivery of public services. However, its success relies on good governance, accountability, and locality-specific policies. This study examined the influence of fiscal decentralization on the provision of water and sanitation services in Pakistan. It targets both provincial-level and urban-rural differentials during 1990–2020. Based on secondary panel data and using the Pooled Mean Group (PMG) estimator in a Panel ARDL environment, the study found that provincial spending has a negative relationship with rural area sanitation services and that provincial revenue has a negative relationship with rural region water services in the long run. In the short term, provincial spending has a positive impact on sanitation facilities at the aggregate level, as well as within the rural region, and provincial revenue has a positive effect on urban sanitation services. Additional provincial-level analysis identifies varied impacts of fiscal decentralization on water and sanitation services. The study suggests an increase in financial transparency, building institutional capacity, improving infrastructure, drainage networks, and ensuring timely and equitable transfers of revenues to provincial governments. The study offers policy suggestions to practitioners for the implementation of decentralization approaches to yield enhanced water and sanitation outcomes in Pakistan.